KETERKAITAN PERSEPSI DAN PERILAKU PENGUNJUNG TERHADAP KESEJAHTERAAN RUSA TIMOR DI TAMAN SATWA CIKEMBULAN GARUT - Anggita Puspitasari; Burhanuddin Masy'ud; Tutut Sunarminto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Rusa deer management in Taman Satwa Cikembulan (TSC) as one of the conservation institution needs to consider animal welfare, perceiption, and behavior of visitors, order to optimize the function of Rusa deer as an exhibition wildlife. The data were collected on March to April 2014 in TSC, Garut, gains by interview and questionnaire. This research shown that animal welfare implementation of Timor deer in TSC rank into sufficient. Health management wasn’t yet optimal and it influence pain and injury aspect has become the lowest value. Visitors behavior wasn’t relate significantly with animal welfare assesment, nevertheless if animal welfare emendation done by manager, it will increase visitors anxiety of Timor deer. Animal welfare emendetaion, management of visitors, additional utilities and infrastructures are some manegement which can minimize the annoying behaviors by visitors in TSC. Keyword : animal welfare, behavior, perception, Rusa deer